Faktor Penerapan Akuntansi Keberlanjutan pada Yayasan Nirlaba - Upi Niarti; Berlian Afriansyah; Neneng Hasanah; Titik Suhartini; Tuti Hermelinda (Akuisisi : Jurnal Akuntansi, 2025)
The factors influencing the implementation of sustainability accounting are measured based on the Webqual 4.0 method, which consists of four latent variables: Financial Management, Funding Source Balance, Donor Relationship Management, and Financial or Economic The analysis tool used is Partial Least Squares- Structural Equation Modeling (PLS-SEM). Model parameter estimation is performed using the PLS-SEM algorithm based on the Ordinary Least Square (OLS) method.Research data were obtained through the distribution of 89 questionnaires to financial managers of non-profit foundations in Rejang Lebong Regency.The analysis results show that Financial Management, Balance of funding sources, and Donor relationship management do not significantly affect the implementation of sustainability accounting, with total influences of 0.149, 0.011, and -0.155, respectively.Meanwhile, the variable of financial or economic approach significantly affects the implementation of sustainability accounting with a total influence of 0.707. While the financial or economic approach variable significantly influences the implementation of sustainability accounting with a total impact of 0.707. Keywords: Sustainability Accounting, Implementation, Green Accounting